2011
DOI: 10.1007/s10709-012-9632-2
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid origin, genetic diversity and population structure in the tetraploid sea lavender Limonium narbonense Miller (Plumbaginaceae) from eastern Spain

Abstract: Limonium narbonense Miller is a fertile tetraploid species with a sporophytic self-incompatibility system. This sea lavender is found in coastal salt marshes which have been under intense human pressure during the past decades resulting in significant habitat fragmentation. Eleven microsatellite loci specifically designed for this species were amplified in 135 individuals from five populations. These markers were used to investigate the polyploid nature, the levels of genetic diversity and population structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 64 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…This finding agrees with the expected results for predominantly selfing species (Vanden Broeck et al, 2014), However,the level of genetic diversity reported in our study was found to be slightly higher than that detected by Vogel et al (2009) andFiliz et al (2009b) in a large Turkish collection of B. distachyon by using SSR and SRAP markers, respectively.Conversely, a relatively low level of genetic diversity was revealed by Hammami et al (2012) in a relatively small Spanish collection of thecomplex of species B. distachyon, B. stacei and B. hybridum (7, 4 and 12 accessions,respectively) by using allozymes, and by Jaroszowicz et al (2012) in a collection of 18Eurasian B. distachyon accessions by using RAPD markers. The high genetic diversityobserved in our study agrees with the expectations for polyploid taxa since it has beendemonstrated that the polyploid species typically display a great genetic diversity (Palop-Esteban et al, 2011).Moreover, our results showed that the observed heterozygosity across the studied populations was lower about three times than the expected heterozygosity (31% vs 79%), whichconfirms that B.…”
Section: Discussionsupporting
confidence: 91%
“…This finding agrees with the expected results for predominantly selfing species (Vanden Broeck et al, 2014), However,the level of genetic diversity reported in our study was found to be slightly higher than that detected by Vogel et al (2009) andFiliz et al (2009b) in a large Turkish collection of B. distachyon by using SSR and SRAP markers, respectively.Conversely, a relatively low level of genetic diversity was revealed by Hammami et al (2012) in a relatively small Spanish collection of thecomplex of species B. distachyon, B. stacei and B. hybridum (7, 4 and 12 accessions,respectively) by using allozymes, and by Jaroszowicz et al (2012) in a collection of 18Eurasian B. distachyon accessions by using RAPD markers. The high genetic diversityobserved in our study agrees with the expectations for polyploid taxa since it has beendemonstrated that the polyploid species typically display a great genetic diversity (Palop-Esteban et al, 2011).Moreover, our results showed that the observed heterozygosity across the studied populations was lower about three times than the expected heterozygosity (31% vs 79%), whichconfirms that B.…”
Section: Discussionsupporting
confidence: 91%
“…Population genetic analyses of polyploid data can be done following either a genotypebased (e.g. Palop-Esteban et al 2011) or phenotype-based (e.g. Obbard et al 2006;Vinson et al 2015) approach and, because information can be lost using either method, and each type of analysis has its own set of assumptions, we compared the results of both approaches (following Kirk et al 2011) for many of our analyses.…”
Section: Analysesmentioning
confidence: 99%
“…Thus, better knowledge of the processes that give rise to hybrid taxa is an important question in the evolutionary biology of emerging pathogens. Understanding the mechanisms that lead to speciation and to the establishment, spread, and evolution of hybrid taxa requires investigation of the identity and genetic variability of parental species and of the directionality and recurrence of the hybridization events (9,10).…”
mentioning
confidence: 99%